How Do Foreign Institutional Investors Enhance Firm Innovation? - Luong, Hoang; Moshirian, Fariborz; Nguyen, Lily; Tian, Xuan; Zhang, Bohui (Journal of Financial and Quantitative Analysis, 2017)
We examine the effect of foreign institutional investors on firm innovation. Using firm-level data across 26 non-U.S. economies between 2000 and 2010, we show that foreign institutional ownership has a positive, causal effect on firm innovation. We further explore three possible underlying mechanisms through which foreign institutions affect firm innovation: Foreign institutions act as active monitors, provide insurance for firm managers against innovation failures, and promote knowledge spillovers from high-innovation economies. Our article sheds new light on the real effects of foreign institutions on firm innovation.